HUBUNGAN ANTARA PENERIMAAN DIRI DENGAN KOMPETENSI INTERPERSONAL PADA REMAJA : Studi Korelasi pada Remaja Tunanetra yang Mengalami Ketunanetraan Tidak Sejak dari Lahir di PSBN Wyata Guna Bandung - Yudi Purwanto, - (2011)
The study was based on various phenomena of self-acceptance that occurred among the blind. Observations in the field reveal a presumption that blind children are not the same as sighted people, so he felt embarrassed when dealing with people beware, because he was afraid of being insulted by people aware of its limitations due to eyesight. The insult would make teenagers with visual impairment have problems in social development, one of which is interpersonal relationships. This research was conducted with the objective of identifying an overview of self-acceptance with interpersonal competence in adolescents who experience blindness not since the birth in order to PSBN Wyata Bandung, in addition to determine whether there is a significant relationship between self-acceptance with interpersonal competence in adolescents who experience blindness does not since the birth in order to PSBN Wyata Guna Bandung. This study uses quantitative research methods with correlational techniques. The research data revealed by using a questionnaire in which the instruments of self-acceptance that will be used by researchers refer to the opinion Sheerer (Cronbach, 1963), while the instrument of interpersonal competence refers to the opinion of Buhrmester and Reis (Nashori, 2008). The population in this study is the boarder PSBN Wyata To Bandung with the study sample totaled 30 people (adolescents with visual impairments who are not from the birth). The sample is determined by the total sampling techniques. The results showed all of the adolescent respondents who experienced blindness are not blind from birth since the PSBN Wyata To Bandung has a level of self-acceptance and interpersonal competence are. Statistical test results showed a correlation coefficient of +0,749 in other words, there is a significant relationship between self-acceptance with interpersonal competence adolescents who experience blindness are not blind from birth.